A CRITIC-CODAS Approach for Ranking WirelessCommunication Technologies in Precision Agriculture: Application to Irrigation System - Khadeejah Adebisi Abdulsalam; Damilare Babatunde; John Adebisi; Olubayo Babatunde (Journal of Digital Food, Energy & Water Systems)
This study evaluates and ranks wireless communication technologies for agricultural irrigation systems using the CRITIC-CODAS multi-criteria decision-making method. Technologies including WSN, LPWAN, LoRa, 5G, IoT, and NB-IoT are compared based on range, power consumption, data rate, coverage, latency, battery life, and device density. The CRITIC method is used to objectively determine criteria weights, with data rate, latency, and battery life emerging as the most important factors. 5G ranks highest with its superior data rate and device density, but its high-power needs may limit suitability for remote agriculture. IoT offers a balanced option across multiple criteria, while WSN excels in power efficiency and battery life. LPWAN, LoRa, and NB-IoT provide excellent range and battery life for wide-area, low-power applications despite lower data rates. The analysis provides a framework for stakeholders to select appropriate technologies based on specific agricultural requirements. Matching wireless technologies to irrigation needs can enhance agricultural sustainability and productivity. Further research could explore technology combinations, cost factors, and real-world testing. This systematic evaluation approach can be extended to other smart agriculture applications to optimize technology adoption.